Design of a pressure vessel shell-bottom closure achieved via a segmented locking ring. (December 2020) - Strozzi, A.; Lugli, R.
Abstract: A simplified mechanical analysis is carried out for a specific closure system of a pressure vessel, consisting of a segmented locking ring, partially inserted into an annular groove; the ring portion radially protruding from the slot supports the vessel bottom; sealing is achieved by placing a copper gasket between the ring and the bottom. Several formulae useful for design purposes are derived. In particular, an approximate contact reaction is assumed, that is formed by a distributed constant linear force and by concentrated forces at the extremities of the ring-slot contact; this assumption allows analytical expressions of the ring internal forces to be obtained. Stress concentrations at the re-entrant corners of the vessel groove are evaluated both numerically and analytically. An approximate formula is developed for forecasting the contact zones between the ring and the groove. A numerical example assessing the design formulae is presented. Highlights: A mechanical analysis is carried out for a closure system of a pressure vessel, consisting of a segmented locking ring. Formulae useful for design purposes are derived. A simplified reaction force between the ring and the groove bottom faces is proposed, and the main stresses are derived. A numerical example assessing the design formulae is presented.